A new approach for convert multiply-connected trees in Bayesian networks - Hussein, Baloochian; Alireza, Khantimoory; Saeed, Balochian (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.